Investigation of structural, energy state and kinetic characteristics of RNiSb semiconductor (R = Gd, Lu) - Romaka, L.P.; Kaczorowski, D.; Нoryn A.M.; Stadnyk, Yu.V.; Krayovskyy, V.Ya.; Romaka, V.V. (Physics and Chemistry of Solid State, 2016)
Peculiarities of structural, energy and kinetic characteristics of p-GdNiSb and p-LuNiSb semiconductors in the temperature range T = 4.2 - 400 K. were investigated. ) to 6% vacancy and partial, to 1.35%, displacement of Ni (4c) atoms by Lu (5d16s2).